시각장애아의 리터러시 향상을 위한 디멘션 확장의 3D프린팅 명화감상 교구 개발 및 적용 효과 - 현은령(Hyun, Eun Ryung) (한국디자인리서치, 2023)
본 연구에서 개발되는 디멘션 확장의 3D프린팅 미술 감상교구는 그동안 평면 형태로 인해 촉각 감상이 불가능했던 명화를 ‘배경, 부주제, 주제’ 등의 순으로 레이어화 한 후 분리하여 3D프린터로 출력한 것이다. 즉, 명화 작품을 단일 레이어에 담았던 방식과 다르게, 각 레이어 별로 인물과 사물, 공간을 분리시켜 디멘션의 개념 이해를 용이하게 할 수 있도록 구성하였다. 2020년부터 2022년까지, 총 3년에 걸쳐 맹학교 2개교를 대상으로 적용한 결과, 시작장애아들은 본 교구를 통해 그동안 평면 형태로 구성되어 감상하기 어려웠던 명화를 적층과 축적의 원리를 통해 제작된 것임을 이해할 수 있게 되었다. 이러한 명화 제작에 대한 이해는 작가와 당시 시대상에 대한 흥미를 가질 수 있도록 하여, 본 교구가 시각장애아들이 세상을 이해하는 리터러시 함양 도구로 활용될 수 있음을 확인하였다. 특히 개발된 본 교구 및 교재는 요구도에 기반한 교육 프로그램의 보조 매체로 제공되어 특수교육 현장에서 시의성과 필요성을 충족시킬 수 있을 것으로 평가되었다. The dimension-expanded 3D printing art appreciation teaching aid developed in this study is a 3D printer that layers famous paintings that have been unable to appreciate touch due to their flat shape in the order of "background, sub-topic, and subject." In other words, unlike the method of putting famous paintings on a single layer, it was organized to facilitate understanding of the concept of dimension by separating people, objects, and spaces for each layer. As a result of applying it to two blind schools over a total of three years from 2020 to 2022, students with starting disabilities can understand that famous paintings, which have been composed in a flat form, were produced through the principle of stacking and accumulation. This understanding of masterpiece production made it possible to have an interest in the artist and the times at the time, confirming that this parish could be used as a literacy cultivation tool for blind children to understand the world. In particular, the developed teaching aids and textbooks were evaluated to be able to meet the timeliness and necessity in the special education field as they were provided as auxiliary media for educational programs based on demand. KCI Citation Count: 2